2005
DOI: 10.1055/s-2004-830444
|View full text |Cite
|
Sign up to set email alerts
|

The Linderniaceae and Gratiolaceae are further Lineages Distinct from the Scrophulariaceae (Lamiales)

Abstract: The Lamiales are one of the largest orders of angiosperms, with about 22,000 species. The Scrophulariaceae, as one of their most important families, has recently been shown to be polyphyletic. As a consequence, this family was re-classified and several groups of former scrophulariaceous genera now belong to different families, such as the Calceolariaceae, Plantaginaceae, or Phrymaceae. In the present study, relationships of the genera Craterostigma, Lindernia and its allies, hitherto classified within the Scro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 42 publications
2
95
1
5
Order By: Relevance
“…이 분류군에 속하는 식물들의 엽록체 유전자들(rbcL, ndhF 및 rps2)의 염기서열을 비교하여 분자유전학적으로 분석하려는 시도가 1990년대에 시작되었는데, 그 결과 종래에 현삼과로 분류되어왔던 식물들을 여러 개의 서로 다른 과로 다시 분류 해야 한다는 의견들이 제시되어서 수용되었다 [3,9,10]. 이 중에 서 국내에 널리 분포되어있는 꽃며느리밥풀(Melampyrum roseum)과 나도송이풀(Phtheirospermum japonicum)은 열당과 (Orobanchaceae)로 옮겨졌고, 물칭개나물(Pseudolysimachion undulata)은 질경이과(Plantagianaceae)로 옮겨졌으며, 주름잎 (Mazus pumilus)은 파리풀과(Phrymaceae)로 재분류되었고, 외풀(Lindernia crustacea)은 외풀과(Linderniaceae)로 재분류되 었으며 [13], 지황은 현재 속하는 과(family)가 모호한 상태이 다. 그러나 주름잎을 파리풀과로 분류하는 것과 외풀을 외풀 과로 분류하는 것에 대해서 나중에 의문이 제기되어 있는 상 태이기 때문에 종래에 현삼과로 분류되었던 꿀풀목 식물들의 분류는 아직도 진행형이라고 볼 수 있다 [12].…”
Section: 서 론 현삼과(Scrophulariaceae)는 19세기부터 존재하던 분류군 으로서 꿀풀목(Lamiales)unclassified
“…이 분류군에 속하는 식물들의 엽록체 유전자들(rbcL, ndhF 및 rps2)의 염기서열을 비교하여 분자유전학적으로 분석하려는 시도가 1990년대에 시작되었는데, 그 결과 종래에 현삼과로 분류되어왔던 식물들을 여러 개의 서로 다른 과로 다시 분류 해야 한다는 의견들이 제시되어서 수용되었다 [3,9,10]. 이 중에 서 국내에 널리 분포되어있는 꽃며느리밥풀(Melampyrum roseum)과 나도송이풀(Phtheirospermum japonicum)은 열당과 (Orobanchaceae)로 옮겨졌고, 물칭개나물(Pseudolysimachion undulata)은 질경이과(Plantagianaceae)로 옮겨졌으며, 주름잎 (Mazus pumilus)은 파리풀과(Phrymaceae)로 재분류되었고, 외풀(Lindernia crustacea)은 외풀과(Linderniaceae)로 재분류되 었으며 [13], 지황은 현재 속하는 과(family)가 모호한 상태이 다. 그러나 주름잎을 파리풀과로 분류하는 것과 외풀을 외풀 과로 분류하는 것에 대해서 나중에 의문이 제기되어 있는 상 태이기 때문에 종래에 현삼과로 분류되었던 꿀풀목 식물들의 분류는 아직도 진행형이라고 볼 수 있다 [12].…”
Section: 서 론 현삼과(Scrophulariaceae)는 19세기부터 존재하던 분류군 으로서 꿀풀목(Lamiales)unclassified
“…Merr. which is known as Pugun tanoh or poguntano by Indonesian people belongs to family Linderniaceae [5,6]. The leaf of plant is traditionally used for helminthiasis treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, doubts arose due to the morphological heterogeneity (Fischer 1992) whether Lindernia was really monophyletic. Molecular phylogenetic studies (Olmstead & Reeves 1995;Olmstead et al 2001;Rahmanzadeh et al 2005;Albach et al 2005) revealed that traditional family Scrophulariaceae is polyphyletic and a new family Linderniaceae was emerged as a separate lineage including Lindernia with its relative genera. A recent study by Fischer et al (2013) on phylogeny of the family Linderniaceae revealed that the genus Lindernia as accepted to date is shown to be polyphyletic and hence, the genera Bonnaya and Vandellia are resurrected together with Lindernia sensu stricto and a new genus Linderniella Eberhard Fischer, Bastian Schäferhoff & Kai Müller (2013: 209).…”
Section: Introductionmentioning
confidence: 99%